Germany : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Germany. (IMF Staff Country Reports; Country Report, 2019)
Germany's economic performance has been strong for the past decade, but external factors and structural challenges are now weighing on growth. The export-dependent economy has been hit by the recent slowdown in global demand, while medium-term growth is expected to fall due to low productivity growth and adverse demographics. External imbalances remain large, partly reflecting rising top income inequality, macro-financial vulnerabilities are rising, and the financial sector continues to suffer from weak profitability. Still, fundamentals are sound, with public and private balance sheets remaining healthy, and the unemployment rate at record lows. Inflation is subdued, but wage growth is continuing to pick up, reflecting the strength of the labor market and increasingly binding capacity constraints.